Deficiency of vitamins C and E in women of childbearing age in Brazil: a systematic review and meta-analysis - Lucchetta, Rosa Camila; Cavicchioli, Sophia de Andrade; Gini, Ana Luísa Rodriguez; Forgerini, Marcela; Varallo, Fabiana Rossi; Nadai, Mariane Nunes de; Fernandez-Llimos, Fernando; Mastroianni, Patricia de Carvalho (São Paulo Medical Journal, 2021)
BACKGROUND: Despite the several options available for supplements containing vitamins C and E, evidence regarding the prevalence of deficiency or insufficiency of these vitamins is weak. OBJECTIVES: To estimate the prevalence of deficiency or insufficiency of vitamins C and and associated factors among women of childbearing age, in Brazil. DESIGN AND SETTING: Systematic review and meta-analysis conducted at a Brazilian public university. METHODS: A search from index inception until May 2020 was conducted. Meta-analyses were performed using inverse variance for fixed models, with summary proportions calculation using Freeman-Tukey double arcsine (base case). Reporting and methodological quality were assessed using the Joanna Briggs Institute tool for prevalence studies. RESULTS: Our review identified 12 studies, comprising 1,316 participants, especially breastfeeding women. There was at least one quality weakness in all studies, mainly regarding sampling method (i.e. convenience sampling) and small sample size. The prevalence of vitamin C deficiency ranged from 0% to 40%. Only vitamin E deficiency was synthetized in meta-analyses, with mean prevalences of 6% regardless of the alpha-tocopherol cutoff in plasma, and 5% and 16% for cutoffs of < 1.6-12.0 mmol/l and < 16.2 mmol/l, respectively. The cumulative meta-analysis suggested that a trend to lower prevalence of vitamin E deficiency occurred in recent studies. CONCLUSIONS: Although the studies identified in this systematic review had poor methodological and reporting quality, mild-moderate vitamin C and E deficiencies were identified, especially in breastfeeding women. Thus, designing and implementing policies does not seem to be a priority, because the need has not been properly dimensioned among women of childbearing age in Brazil. REGISTRATION NUMBER IN PROSPERO: CRD42020221605.